Identidade da mulher moçambicana nas obras de Noémia de Sousa e Paulina Chiziane - Dantas, Luciana Neuma Silva Muniz Meira (2011)
This work aims to analyse the representation of Mozambican woman s voice during the Portuguese domination that made million of Africans slaves, injecting the inferiority of black race and the superiority of white race and culture, it was named civilized. During the period of colonization the presence of Portuguese in Mozambique affected the Mozambicans life mainly the woman who suffered with racial discrimination and devalorization caused by a created image, it is wild and obscene. In face of this negative image, the Mozambican woman could fight through of resistance thought against this imposition. However, the feminine literary writing of Noémia de Sousa and Paulina Chiziane give voice to the Mozambican woman, valorizing and breaking this unreal image to put an end on the subalternity which empower her silence. Their texts, represents the woman like Mother-Africa, the mother of all Mozambican women. Finally, to analyse the Mozambican woman s voice in post-colonial period and the aspects of the conquest of independence that influenced the post-modern identity like memory and national conscience.